Petal-Graphyne: A novel 2D carbon allotrope for high-performance Li and Na ion storage - Lima, Kleuton A.L.; Laranjeira, José A.S. [UNESP]; Martins, Nicolas F. [UNESP]; Dias, Alexandre C.; Sambrano, Julio R. [UNESP]; Galvão, Douglas S.; Ribeiro, Luiz A. (Elsevier, 2025)
Using density functional theory simulations, this study introduces Petal-Graphyne (PLG), a novel multi-ring metallic structure composed of 4-, 8-, 10-, and 16-membered rings. Its structural, electronic, and lithium/sodium storage properties were comprehensively investigated. PLG exhibits a high theoretical capacity of 1004mAh/g for Li, Na, and mixed-Li/Na-ions, surpassing conventional graphite anodes. The material remains metallic, with multiple band crossings at the Fermi level. The optimal energy barriers for Li (0.28eV) and Na (0.25eV) on PLG and favorable diffusion coefficients in both monolayer and multilayer configurations are unveiled. The open circuit voltages are 0.47V for Li, 0.51V for Na, and 0.54V for mixed-ion storage, suggesting stable electrochemical performance. These results highlight PLG as a promising candidate for next-generation lithium and sodium-ion batteries, combining high storage capacity and efficient ion transport.